A Three-Decade Analysis of the Public Policy Impact on Violence Against Women - Lindawati, Lindawati; Larasati, Endang; Rina Herawati, Augustin (Iapa Proceedings Conference, 2024)
Violence against women (VAW) is a global issue that causes physical and psychological harm and hinders women's participation in various life aspects, impeding a country's development and economy. In this regard, research on the issue tends to focus on health, socio-economic, or legal aspects and prevention, overlooking the impact of public policy on VAW. This study utilises bibliometric analysis to investigate the impact of public policy on VAW over the last three decades. The sample analysed was 405 articles. The results show that the literature production in this field tends to increase yearly. Despite the issue being more prevalent in low- and middle-income countries, research is predominantly conducted by developed countries, with the US, UK, and Canada being the most influential. Public policies have both direct and indirect impacts on women. Policies can create social conditions that increase gender equality, encouraging improvements in women's social and economic conditions. On the other side, public policy can increase women's vulnerability to violence. It is an urge to address VAW that tends to increase due to the COVID-19 pandemic. Thus, it is essential to critically evaluate policy implementation and ensure women can access various forms of protection and assistance.